Absorption based size characterisation of aerosol by using photoacoustic spectroscopy. (1st July 2023) - Ajtai, T.; Hodovány, Sz; Schnaiter, M.; Szabó, G.; Bozóki, Z.
Abstract: The size of the atmospheric soot is a critical parameter in many perspectives starting from climate impact through health relevance ended with air quality regulations. In this study, we propose a novel methodology for soot selective size measurement of atmospheric aerosol. The proposed method is based on the synergy of selectivity of the aerosol photoacoustic (PA) spectroscopy for highly absorbing atmospheric components and size dependency of the measured phase of the PA signal. The proposed experimental set-up is based on the instrument combination of 4λ-PAS and scanning mobility particle sizer (SMPS) in a closed loop arrangement. We experimentally demonstrated here, first that the PA phase of the photoacoustic signal depends on the characteristic size of the soot aerosol. In order to better understand the effect of morphology, nigrosine particles with spherical shape are also studied. The comparison of the measured data and the theoretical calculation is also investigated. Comparison of the theoretical simulation and the measured data shows increasing differences towards the higher size of the measured aerosol in all samples. We also demonstrated that the inherent system phase is independent of the phase shift related to particles. Highlights: Novel method for selective size measurement of light absorbing carbonaceous particulate matter in the atmosphere. Experimental verification of the particle size dependency of the photoacoustic signal. Comparison of the theoretical calculation and measured data.